Analisis Saluran, Margin, Dan Efisiensi Pemasaran Ternak Sapi : Studi Kasus Pedagang Ternak Sapi - Maulana Malik Ibrahim (Jurnal Riset Multidisiplin Edukasi, 2025)
Background: The increase in population and living standards has led to high demand for beef in Indonesia, including in Tanjung Jabung Barat Regency. This situation requires an increase in livestock population and marketing channel efficiency. However, cattle marketing in Senyerang Subdistrict is still dominated by middlemen, resulting in high marketing margins and low bargaining power for farmers. Purpose: This study aims to determine the patterns of cattle marketing channels, calculate marketing margins, and assess marketing efficiency (farmer's share) in each marketing channel in Senyerang District. Methods: The research was conducted using a survey method with a case study approach. Respondents consisted of three farmers selected using simple random sampling and four traders selected using census sampling. Primary data was obtained through interviews using structured questionnaires and field observations, while secondary data was obtained from relevant agencies and BPS publications. The analysis was descriptive to describe the characteristics of the marketing channel, as well as quantitative to calculate the marketing margin and farmer's share. Results: The study found two marketing channel patterns in Senyerang Subdistrict, namely channel I (farmer–consumer) and channel II (farmer–collector–consumer). No marketing margin was found in channel I (0%), while in channel II it was recorded at IDR 1,250,000 per head or 7.04%. The efficiency level of the farmer's share in channel I reached 100%, while in channel II it was 92.59%. Conclusion: Marketing channel I is more efficient because it does not involve intermediaries and provides a higher farmer's share to livestock farmers. Conversely, channel II tends to be less efficient due to additional marketing costs and larger margins at the trader level. This study emphasizes the importance of strengthening direct market access for livestock farmers in order to optimize income and create a more equitable marketing system.